IMPLEMENTATION OF PT TELKOM PARTNERSHIP PROGRAM IN THE SME EMPOWERMENT FRAMEWORK - ., Masruddin (The International Journal of Accounting and Business Society, 2017)
This study aims to find out in depth the procedure of implementation of partnership program conducted by PT. Telkom in order to empower SME (Small and Medium Enterprises) in Palu city of Central Sulawesi, Indonesia. In addition, this study also wanted to know how the influence of the implementation of partnership programs on the power of SMEs that become partners. This study was conducted for 8 months. This study uses a qualitative approach in the realm of interpreative paradigm. The research method used to collect and analyze data is by observation and direct interview in PT Telkom branch of Palu.The results of this study indicate that the existence of this partnership program, some people in the city of Palu who know the program feel very helpful. There are several weaknesses and obstacles encountered in the implementation of this partnership program, among others: first, CDC Unit has not been fully able to analyze the proposal from prospective partner of PT Telkom. Secondly, the absence of financial records of SMEs, so that SMEs are difficult to know and determine the turnover of its business. Third is the lack of effective coaching is done, because coaching is only done before the signing of the contract (initial crediting), not intensified byÂ  Telkom during the contract runs. Fourthly, there is still no transparency from Telkom related to the prospective partners who were accepted and rejected even though they have met the requirements. This resulted in the presupposition of the prospective partners assisted by the existence of the lack of independence from Telkom. Fifth, the implementation of 5C in the partnership program has not run optimally, this is also due to the lack of employees who handle it optimally. Sixthly, there are still partners who are less serious by utilizing the facilities provided by PT Telkom partnership program.